Comparison of sounds and words as sample stimuli for discrimination training. Issue 3 (23rd March 2021) - Halbur, Mary; Kodak, Tiffany; Williams, Xi'an; Reidy, Jessi; Halbur, Christopher
Abstract : A portion of children diagnosed with autism spectrum disorder (ASD) have difficulty acquiring conditional discrimination. However, previous researchers suggested that the discrimination of nonverbal auditory stimuli may be acquired more efficiently (Eikeseth & Hayward, 2009; Uwer, et al., 2002). For example, a child may learn to touch a picture of a piano after hearing the musical instrument more quickly than when the auditory stimulus is the spoken word "piano." The purpose of the present study was to extend previous research by assessing the acquisition of conditional discriminations with sample stimuli presented as either automated spoken words or high‐ and low‐disparity nonverbal auditory stimuli (i.e., environmental sounds). Conditional discriminations with high‐disparity environmental sounds as sample stimuli were acquired rather than or more efficiently than those trained with low‐disparity environmental sounds and words as sample stimuli.